Thinking Inside the Box: Graduate Students’ Perspectives on Hindered Creativity - Michelle N. Anderson (Adult Education Research Conference, 2009)
This phenomenological study focused on the lived experiences of adult graduate students in relation to creativity. Findings illuminate the influence of professors on educational experiences of hindered creativity.
Keywords: Adult learning; creativity; phenomenology